Droplet digital PCR of tumor suppressor gene methylation in serial oral rinses of patients with head and neck squamous cell carcinoma. Issue 6 (17th February 2021) - Fung, Sherwood Y. H.; Chan, Kwan Chee Allen; Wong, Eddy W. Y.; Ng, Cherrie W. K.; Cho, Ryan; Yeung, Zenon W. C.; Lam, Jacky W. K.; Chan, Jason Y. K.
Abstract: Background: Head and neck squamous cell carcinoma (HNSCC) currently lacks sensitive approaches to detect cancer‐related traits in body fluid. Methods: Methylation of tumor suppressor genes (TSGs) ( PAX5, EDNRB, and DCC ) were measured in the oral rinses from 50 HNSCC and 58 control subjects using droplet digital PCR (ddPCR). Diagnostic accuracies in detecting HNSCC and the detection rate of recurrence in the post‐treatment monitoring were analyzed. Results: ddPCR TSG methylation detection in oral rinses for diagnosis of HNSCC had an AUC of 0.892 for PAX5, 0.753 for EDNRB, and 0.729 for DCC . Significant drop of TSG methylation was observed after completion of surgery ( p < 0.01). 76.9% of the relapse cases had a pre‐emptive rebound of methylation above presurgery levels in at least one of the tested markers before confirmed recurrence. Conclusions: Utilizing ddPCR for TSG methylation detection in oral rinses shows potential for detection and monitoring of HNSCC.